Reanálisis: Una alternativa para potencializar el uso de datos de investigación. - Beltrán Peña, N Yaneth (Ingeniería, 1999)
The objective of the present review is to give a look to the theoretical and practical precedents and to the methodological basis of the Secondary Analysis or Re-analysis as alternative of investigation; for such effect it is based on epistemologic principles of incompleteness, intersubject validation and narrowminded investigator, in addition to an answer to Serendipity's atittude in contraposition to the possibilty of verifyng knowledge. In the secondary analysis methodology it uses equivalent scientific methods, beginning whit the identification of the investigation problem and its theoretical basis, followed by the objectives and hypothesis formulation and the re-calculation of the original data, their findings are interpreted to the light of the original hypothesis as much of the new hypothesis, and the terciary analysis, or Meta-analysis, is that in which information is based on the primary analysis but whose objective is to make synthesis of previus investigations and because of this it is centered in summar y statistics.